Money over mastery, family over freedom : slavery in the antebellum upper South - Schermerhorn, Calvin, 1975- (Studies in early American economy and society from the Library Company of Philadelphia., 2011)
Slaves focused their energy and attention, however, not on making money, as slaveholders increasingly did, but on keeping their kin out of the human coffles of the slave trade.